Mechanism of immunomodulatory drugs in multiple myeloma - Sedlarikova, Lenka; Kubiczkova, Lenka; Sevcikova, Sabina; Hajek, Roman (Leukemia research, 2012)
Multiple myeloma is the second most common hematological cancer in the world. It is characterized by accumulation of malignant plasma cells in the bone marrow, osteolytic lesions and monoclonal immunoglobulins in blood/urine. With the introduction of immunomodulatory drugs into the treatment protocol, the outcome of multiple myeloma patients has dramatically improved with more than 30% of patients surviving for 10 years thus shifting multiple myeloma to a treatable condition.
Keywords: Animals; imunologické faktory; lidé; Multiple Myeloma; zvířata; Immunologic Factors; mnohočetný myelom; Humans